Non-enzymatic browning and estimated acrylamide in roots, tubers and plantain products - Quayson, E.T.; Ayernor, G.S. (Food Chemistry, 2007)
Acrylamide has been discovered in foods, especially high carbohydrate foods that are dry-cooked (baked, fried or roasted) at high temperatures which also create the conditions for non-enzymatic browning. Baking, frying and roasting are common food preparation methods in Ghana. Fifteen different high carbohydrate foods in Ghana, that undergo dry-cooking, have been investigated for non-enzymatic browning and acrylamide production. The products that showed notable non-enzymatic browning and acrylamide levels include fried sweet potato, plantain chips from the fresh produce, with their respective non-enzymatic browning and acrylamide values as 0.095 ± 0.006 optical density (OD), 1043 ± 47.6 parts per billion (ppb); 0.034 ± 0.03 OD, 568 ± 22.9 ppb. Roots and tuber products had relatively high non-enzymatic browning and acrylamide levels while plantain products showed low levels of non-enzymatic browning and acrylamide. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Acrylamide; Dry-cooking; Non-enzymatic browning